Reliability of a non-invasive method to calculate buffer capacity after exhaustive cycling exercise of 20 s to 12 min: a pilot study - Gehlert, Sebastian; Khurshudyan, Asatur; Weber, Sebastian; Widdershoven, Jochem; Van Schuylenbergh, Reinout (Frontiers in Sports and Active Living, 2025)
Traditionally, buffer capacity (β) is measured on muscle biopsies by measuring changes in muscle pH in relation to exposure of standardized quantities of hydrochloric acid. This is an invasive approach requiring specific equipment and trained personnel which limits its usability in a normal training context. Assessing β using capillary blood lactate concentration (BLC) and pH values has been proposed as a more practical and cost-effective approach. The reliability of the input BLC and pH data on the calculations of β after maximal sprint and endurance exercise has not yet been investigated and was major aim of our study. Eleven subjects performed six maximal performance tests ranging from 20 s to 12 min duration over a 2-week period. All subjects were familiarized with the test conditions. For each performance test, pre and posttest BLC and pH was measured and used to calculate β using the Henderson-Hasselbach equation. As BLCpre and pHpre values showed poor reliability, β calculations were repeated using constants for BLCpre (1.23 mmol·L−1) and pHpre (7.426) chosen from the average values in the experimental data. Test-retest reliability for BLCpre (ICC: 0.12, 95% CI −0.49–0.65, n.s.) and pHpre (ICC: 0.40, 95% CI −0.22–0.79, n.s.) was poor, whereas BLCpost (ICC: 0.95, 95% CI 0.82–0.99, p < 0.05) and pHpost (ICC: 0.89, 95% CI 0.65–0.97, p < 0.05) displayed good to excellent reliability. Good reliability was observed for β calculated from the Henderson-Hasselbalch equation utilizing BLCpost and pHpost only (ICC: 0.86, 95% CI 0.55–0.96, p < 0.05). The validity of this method in comparison with gold-standard methods needs further scientific investigation.